(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Regeneration of the bone loss as a consequence of periodontal disease can be achieved by using bone regenerative material, several autogenous and alloplastic materials are being used for the main purpose of reconstruction of osseous tissue in grade 2 furcation defects. There is paucity on published literature on demineralized freeze dried bone grafts (DFDBA) and hydroxyapatite (HA) in the management of grade 2 furcation defect management. A 45-year-old patient-reported pain in both the left and right lower back region of the jaw and want to get treated. The final diagnosis was Generalized chronic stage 2 and grade 3 periodontitis and bone graft materials were placed accordingly in the sites to be treated and there were positive outcomes in both sites with no significant difference when compared with each other. The use of both bone graft materials aids in bone fill, there are better results observed in site treated with DFDBA.